Renewable Energy, Agriculture and CO2 Emissions: Empirical Evidence From the Middle-Income Countries - Majewski, Sebastian; Mentel, Grzegorz; Dylewski, Marek; Salahodjaev, Raufhon (Frontiers in Energy Research, 2022)
This study explores the effect of renewable energy and agriculture on CO2 emissions in a sample of 94 middle-income countries for the years 2000–2015. Using two-step generalized method of moments (GMM) regression, we find there is a negative relationship between renewable energy production, agriculture value added and per capita CO2 emissions. If causal, a 1% increase in renewable electricity output leads to a 0.18% decrease in CO2 emissions. Our results remain robust when we include additional control variables. Our study suggests that policy tools such as subsidies or low interest loans can be used to promote renewable energy consumption in middle-income countries.